Outcomes associated with mammalian target of rapamycin (mTOR) inhibitors in heart transplant recipients: A meta-analysis. (15th August 2018) - Jennings, Douglas L.; Lange, Nicholas; Shullo, Michael; Latif, Farhana; Restaino, Susan; Topkara, Veli K.; Takeda, Koji; Takayama, Hiroo; Naka, Yoshifumi; Farr, Maryjane; Colombo, Paolo; Baker, William L.
Abstract: Background: Data evaluating mTOR inhibitor use heart transplant (HT) patients comes from relatively small studies and controversy exists regarding their specific role. We performed a meta-analysis of randomized trials to evaluate the efficacy and safety of mTOR inhibitors in HT patients. Methods: We performed a systematic literature search of Medline and Embase through July 2017 identifying studies evaluating mTOR inhibitors in HT patients reporting effects on coronary allograft vasculopathy (CAV), renal function, acute cellular rejection (ACR), cytomegalovirus (CMV) infection, and discontinuation due to adverse drug events (ADE). Data were pooled using a random-effects model producing a mean difference (MD; for continuous data) or odds ratio (OR; for dichotomous data) and 95% confidence interval (CI). Results: 14 trials reported at least one outcome of interest. Change in mean maximal intimal thickness was significantly reduced with mTOR (−0.04 [−0.07 to −0.02]) compared to calcineurin inhibitor/mycophenolate mofetil (CNI/MMF). Rates of CMV infection were also significantly reduced (0.26; [0.2 to 0.32]) with mTOR regimens compared to CNI/MMF therapy. ACR was more frequent with CNI-sparing regimens 6.46 [1.55 to 26.95]). eGFR was significantly improved with CNI-sparing therapies (mean difference 12.09 mL/min [2.43 to 21.74]), but was similar between CNI/mTOR versus CNI/MMF regimens (p > 0.05). Rates of discontinuation due to ADE were higher in mTOR-containing regimens (OR 2.15 [1.28 to 3.60], p = 0.01), while mortality rates were similar (OR 0.91 [0.61 to 1.37], p = 0.62). Conclusions: mTOR-containing regimens can attenuate CAV and CMV risk in HT recipients. A mTOR/MMF combination preserves renal function but increases the risk of ACR. Highlights: The role of mTOR inhibitors in heart transplant remains unclear. Meta-analysis can help define this role. mTOR inhibitors reduce mean maximal intimal thickness versus calcineurin inhibitors. CMV infection occurs less often with mTORs. mTOR can help preserve kidney function.